NADPH oxidase inhibitors: a decade of discovery from Nox2ds to HTS - Cifuentes-Pagano, Eugenia (Cell Mol Life Sci, 2012)
NADPH oxidases (Nox) are established as major sources of reactive oxygen species (ROS). Over the past two decades, Nox-derived ROS have emerged as pivotal in the development of myriad diseases involving oxidative stress. In contrast, Nox are also involved in signaling mechanisms necessary for normal cell function. The study of these enzymes in physiological and pathophysiological conditions is made considerably more complex by the discovery of 7 isoforms: Nox1 through 5 as well as Duox1 and 2, each with its own specific cytosolic components, regulatory control mechanisms, subcellular localization and/or tissue distribution. A clear understanding of the role individual isoforms play in a given system is hindered by the lack of isoform-specific inhibitors. In animal models, knockdown or knockout methodologies are providing definitive answers to perplexing questions of the complex interplay of multiple Nox isoforms in cell and tissue signaling. However, the complex structures and interactions of these heteromeric isozymes predict pleiotropic actions of the Nox subunits and thus suppression of these proteins is almost certain to have untoward effects. Thus, as both therapies and pharmacological tools, molecule-based inhibitors continue to prove extremely useful and rational in design. Unfortunately, many of the available inhibitors have proven non-specific, falling into the category of scavengers or inhibitors of more than one source of ROS. Here, we will review some of the efforts that have been undertaken to develop specific inhibitors of NADPH oxidase over the past decade, from the peptidic inhibitor Nox2ds-tat to more recent small molecule inhibitors that have emerged from high-throughput screening campaigns.